Vellozia gigantea (Velloziaceae) e seus fungos endofíticos: diversidade e bioprospecção de substâncias bioativas - Mariana Costa Ferreira (2017)
Endophytic microorganisms, those residing asymptomatically within plant tissues for at least one period of their life cycle, may have different effects on the ecology of the host plant, its healthy state and its evolution. These microorganisms have been studied for their ability to produce different bioactive metabolites of interest in medicine and agriculture. Among the target plants for studies of the endophytic fungi community, those considered endemic seem to represent a promising alternative for the characterization of rare and/or bioactive molecule producers. In this context, the plant species Vellozia gigantea N.L. Menezes & Mello-Silva (Velloziaceae), a recently described monocotyledon, endemic to Brazil and considered rare, with its history and biology little known until the present moment represents an interesting target for obtaining associated endophytic fungi. From the above, the present work aims to know the diversity of the community of endophytic fungi associated with V. gigantea, as well as to evaluate its capacity to produce bioactive metabolites. Fragments of the leaves and adventitious roots of V. gigantea were surface disinfested and used for the isolation of endophytic fungi. From the sampled material were obtained 326 isolates, 321 filamentous fungi and five yeasts, which were grouped from their morphological and molecular characteristics. Fungi identification was performed by sequencing the internal transcribed region ITS-5.8S of the rRNA gene region, as well as by the partial sequencing of the β-tubulin gene, RNA polymerase II. At the end of the identification process, 84 distinct taxonomic units (UTD) were characterizeds, which belong to the Ascomycota phylum. The Sordariomycetes class was predominant representing 81% of the isolates obtained, followed by Dothideomycetes with 12%. The classes Leotiomycetes (4%) and Eurotiomycetes (2%) were also found, but less frequently. Inserted in Sordariomycetes were found the genera Clonostachys, Colletotrichum, Daldinia, Diaporthe, Fusarium, Trichoderma, Muscodor, Nigrospora, Pestalotiopsis, Neopestalotiopsis and Xylaria. Among the Dothideomycetes were identified the genera Bipolaris, Peyronellaea, Paraconiothyrium, Pallidocercospora, Mycosphaerella, Guignardia and Pseudocercospora. As representatives of the class Leotiomycetes were found taxa belonging to the genus Pezicula, Coccomyces, Myxotrichum and a taxon identified within the order Helotiales. In Eurotiomycetes, species belonging to the genus Penicillium and a taxon classified within the family Herpotrichiellaceae were characterized. Yeasts Yamadazyma michaelii, Lodderomyces (Candida) parapsilosis, as well as a new species identified as Yamadazyma riverae sp. Nov. When compared to correlated studies, the diversity of the endophytic fungi associated with V. gigantea was high (Fisher-α = 42.68), with great species richness (Margalef = 15,21) and absence of taxon dominance (Simpson = 0.96). In order to evaluate the production capacity of bioactive metabolites, the fungi were cultivated in BDA for 15 days and their metabolites extracted with the dichloromethane solvent. The extracts obtained were evaluated for antimicrobial and antiparasitic activity by the plate microdilution method, and chemically characterized for the determination of the bioactive compounds. From the extract of Diaporthe miriciae UFMGCB 9720, which showed antimalarial potential, the compound epoxycyclalasin H was identified, showing activity at concentrations of 51.7 and 39.3 ng / mL against P. falciparum chloroquine sensitive (D6) and to P. falciparum Chloroquine resistant (W2), respectively, activity is never previously reported for this molecule. From the fungal extracts of Trichoderma effusum UFMGCB 9736, Penicillium adametzii UFMGCB 9829 and 9894, Penicillium quebecense UFMGCB 9928, were identified by Gas Chromatography coupled to Flame Ionization Detector (GC-FID), differetns fatty acid (caproic, palmitic, palmitolytic, stearic, oleic and linoleic). The biotechnological potential of the leaves and adventitious roots of V. gigantea was also evaluated. From the extract of the adventitious roots, we isolated four new diterpenes (8 (9), 15-isopimaradien-1,3,7,11-tetraone, 7-oxo-8,11,13-cleistanthatrien-3-ol, 20-epoxy-7-oxo-8,11,13- cleistanthatrien-3-ol, and 20-nor-3,7-dioxo-1,8,11,13-cleistanthatetraene-10-ol) with potential phytotoxic and pesticide activities. From the results obtained is possible to affirm that leaves and roots of V. gigantea, an endemic species of Campo Rupestre of the state of Minas Gerais, Brazil, harbor a community of highly diverse endophytic fungi with potential metabolite-producing fungi Bioactives. In addition, the plant tissues of V. gigantea demonstrate to be source of new metabolites of interest in agriculture.